Analysis of upper and lower limb movement in infants in response to optic flow - preliminary research - Pawlak-Andryszczyk, Żaneta; Andryszczyk, Marek; Topoliński, Tomasz; Sobieska, Magdalena (Journal of Education, Health and Sport, 2022)
Introduction: optic flow is studied in many scientific areas such as automation, robotics, biomechanics and neuropsychology. People who are not visually impaired use this mechanism to move around, usually without realising its complexity. It consists of information provided by the sense of sight and analysed in the central nervous system about the speed and direction of a moving object and the direction and amplitude of the angular and linear components of one’s body. However, little is known about how this mechanism develops in the young child. Objective: Observation of upper and lower limb movement in infants between 4 and 12 weeks. of age under the influence of optic flow stimulation as a stimulus. Development of an optimal test protocol and adaptation of the author’s research station. Material and method: 16 infants aged from 4 to 12 weeks were initially invited to the study, of which 14 infants were finally included in the study group. The motor response test consisted of two stages. Stage I (static trial): the stimulus was a stationary black and white chessboard pattern; stage II (dynamic trial): the chessboard pattern moved toward the child at a speed of 0.17m/s. Cameras recorded the test in both stages. Results: the children showed increased limb movement under the influence of optical flow (test stage II: dynamic test) compared to stimulation with a fixed pattern (test stage I: static test). Conclusions: a response to dynamic versus static stimuli was observed in 11 of 14 children, but testing in one-month-olds is unreliable due to poor head control.